Pengaruh Bantuan Pemerintah terhadap Efisiensi Teknis Pertanian Padi di Provinsi Jawa Timur - Rachman Hakim; Gazali Gazali (AGRIMOR, 2022)
The productivity of rice plants has decreased over the last few years in East Java Province. This needs attention because rice is a staple food. This study aims to measure the efficiency of rice farming in East Java and to determine the effect of access to credit, education, agricultural extension, farmer group membership, age, and government assistance on rice farming efficiency. The data source comes from the Agricultural Survey published by the Central Statistics Agency of East Java Province. Rice farmer households used in this study were 8603 samples. The research method uses Data Envelopment Analysis (DEA) to measure the technical efficiency of rice farming and tobit regression (two limit tobit) to determine the factors that affect the technical efficiency of rice farming. Based on the results of the study, it was found that the technical efficiency of rice farming in East Java was very low, at 0.267. Meanwhile, the results of the two limit tobit estimation show that the technical efficiency of rice farming in East Java is significantly influenced by the variables of education, age, counseling, and government assistance. The variables of farmer group membership and credit have no significant effect.